Impact of a newly constructed motor vehicle road on altitude illness in the Nepal Himalayas. - Reisman, J; Deonarain, D; Basnyat, B (Elsevier, 2017)
Objective This study investigates the impact of motor vehicle travel along a newly constructed road from Besisahar (760 m) to Manang ( 3540 m) in Nepal on altitude sickness (including acute mountain sickness (AMS), high altitude cerebral edema (HACE) and high altitude pulmonary edema (HAPE)). Methods We enrolled all patients diagnosed with altitude sickness in the Himalayan Rescue Association (HRA) Manang clinic in fall 2016. Phi coefficients were calculated to test for an association between Nepali ethnicity and rapid ascent by motor vehicle. A retrospective chart review looked at all altitude sickness patients from 2010 to 2016. Results In fall 2016, more than half (53.8%) of altitude sickness patients traveled to Manang by motor vehicle, and one-third (33%) reached Manang from low altitude Besisahar in 2 or fewer days. Nepali ethnicity had a significant association with motor vehicle travel (phi +0.69, p<0.0001), as well as with rapid ascent to Manang (phi +0.72, p<0.0001). Compared to previous seasons, fall 2016 saw the highest number of patients with altitude sickness, as well as the highest number of patients traveling to Manang by vehicle and reaching Manang in 2 or fewer days, all showing a significant increase comprared to season prior to the road’s completion (p=0.0001, p<0.0001 and p<0.0001, respectively). Conclusions Rapid ascent by the newly- constructed road from Besisahar to Manang appears to be related to a significant increase in the number of patients with all forms of altitude sickness, especially among Nepalis. An educational intervention is urgently needed.